2D Materials - Wongchoosuk, Chatchawal; Seekaew, Yotsarayuth (IntechOpen, 2019)
Two-dimensional (2D) materials have attracted a great deal of attention in recent years due to their potential applications in gas/chemical sensors, healthcare monitoring, biomedicine, electronic skin, wearable sensing technology and advanced electronic devices. Graphene is one of today's most popular 2D nanomaterials alongside boron nitrides, molybdenum disulfide, black phosphorus and metal oxide nanosheets, all of which open up new opportunities for future devices. This book provides insights into models and theoretical backgrounds, important properties, characterizations and applications of 2D materials, including graphene, silicon nitride, aluminum nitride, ZnO thin film, phosphorene and molybdenum disulfide.